2015
DOI: 10.1016/j.ophtha.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in Dark Adaptation Are Associated with Age-Related Macular Degeneration Severity and Reticular Pseudodrusen

Abstract: Purpose We investigate whether ocular and person-based characteristics are associated with dark adaptation (DA) measured using the AdaptRx™ device (Apeliotus Technologies, Atlanta, GA). Design Cross-sectional, single-center, observational study. Participants 116 participants >50 years with a range in age-related macular degeneration (AMD) severity. Methods Participants underwent best-corrected visual acuity (BCVA) testing, ophthalmoscopic examination and multimodal imaging. Presence of reticular pseudodr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
216
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(237 citation statements)
references
References 33 publications
17
216
2
2
Order By: Relevance
“…3,13,14 While we found a significant delay in RIT at follow-up, the exact magnitude of the increased RIT in eyes with RPD could not be estimated in our study because many of the test points were already severely abnormal and failed to reach the rod criterion level within the 20 minutes after an approximate 30% bleach. Nevertheless, iAMD eyes with RPD consistently had a greater proportion of test points with longer RIT or test points that failed to reach the criterion level compared to iAMD without RPD.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…3,13,14 While we found a significant delay in RIT at follow-up, the exact magnitude of the increased RIT in eyes with RPD could not be estimated in our study because many of the test points were already severely abnormal and failed to reach the rod criterion level within the 20 minutes after an approximate 30% bleach. Nevertheless, iAMD eyes with RPD consistently had a greater proportion of test points with longer RIT or test points that failed to reach the criterion level compared to iAMD without RPD.…”
Section: Discussioncontrasting
confidence: 66%
“…1 The cause of this symptom appears to be associated with the impairment or loss of rod photoreceptors, as studies assessing rod function using dark adaptation show that rod-mediated dark adaptation (DA) parameters are markedly abnormal in eyes with early stages of AMD. [2][3][4][5] In addition, histologic studies demonstrated a decline in rod density in AMD eyes. 6,7 Studies have also shown that the magnitude of rod dysfunction increases with increasing AMD severity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although this study examined static rod function, our findings are in agreement with those reported in previous studies where rod recovery was assessed. 19,26,27 In addition, we have further shown that static rod function of iAMD cases without SDD was indistinguishable from control cases when tested without photobleach. A difference in static rod function between iAMD without SDD and control group was only observed when tested with preceding photobleach.…”
Section: Discussionmentioning
confidence: 56%